Substituição do milho por milheto sobre as características de carcaça e carne de novilhos confinados de diferentes predominâncias genéticas - Silva, Rodrigo Medeiros da (2013)
This study aimed at assessing the carcass and meat traits as well as fatty acid profile of crossbred steers of European or zebu genotypic predominance, finished in feedlot, fed diets with high percentage of concentrate (80%) containing different levels of grounded millet grain as replacement for grounded corn grain (0, 33, 66 and 100%). We allocated in 16 collective pens 45 steers with European predominance and 44 with zebu-predominance, with average initial weight of 317.8 and 320.7 kg, respectively, and average age of 21 month. At the end of the finishing period, we slaughtered six animals of each genetic group, randomly chosen within each level of replacement of corn by millet grain. The experimental design was completely randomized with treatments in a 4x2 factorial arrangement using six replicates. The replacement of corn grain by millet grain did not significantly affect slaughter weight (480.4 kg), hot carcass weight (259.5 kg), carcass yield (54.1%) and subcutaneous fat thickness (3.95 mm). Steers with predominant European genotype showed significantly higher values for slaughter weight (507.6 vs. 453.3 kg), hot carcass weight (269.6 vs. 249.3 kg) and Longissimus dorsi area (65.34 vs 56.83 cm2); however, they had lower carcass yield (53,2 vs. 55,00%). Increasing the proportion of millet in the diet linearly increased the arachidic (C20:0), heneicosanoic (C21:0), linolenic (C18:3 n-3) and di-homo linolenic (C20:3 n-6) fatty acids. European steers meat showed less content of myristic (C14:0), heneicosanoic (C21:0) and linolenic (C18:3 n-6) fatty acids. The total concentration of saturated (45.2%), monounsaturated (41.2%) and polyunsaturated (8.7%) fatty acids and, monounsaturated/saturated (1.09) and polyunsaturated/saturated (0.18) relationship were not affected by the factors studied. Millet grain can be used in replacement of corn grain for finishing steers since it does not change carcass traits of economic interest. The increase in the percentage of millet grain in the diet of European and zebu crossbred steers improves the ratio between n-6/n-3 fatty acids.